LANDASAN PENGEMBANGAN SUBSTANSI MANAJEMEN PENDIDIKAN DASAR DALAM PERSPEKTIF ISLAM - Zuhriyah, Indah Aminatuz (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
In order to widespread the best quality of education in elementary education from preliminary to elementary school, it is important to develop the management of education substantion. The aspects of management education substatntion are: 1) curriculum, 2) the student, 3) the teachers, 4) education facilities, 5) education financing, 6) public relation. This paper discussing only 3 aspects, are: 1) development of curriculum which relates to the basic program of children learning for the 0-12 years old, 2) development of students which relates to effective learning process in order to develop children potential for the preliminary and elementary school year age equally, 3) development of teachers which relates to the teachers capabilities in preliminary and elementary years old. Those three aspects is strengthened by al-Qur`an perspective.Keywords: Management substantion, elementary education